Years of Life Lost Due to Premature Death and Their Trends in People With Selected Neurological Disorders in Shanghai, China, 1995–2018: A Population-Based Study - Luo, Zheng; Lv, Huihui; Chen, Yichen; Xu, Xiaoyun; Liu, Kangyong; Li, Xiaopan; Deng, Yang; Zhou, Yi (Frontiers in Neurology, 2021)
Background: Neurological disorders are the leading cause of long-term disability and the second leading cause of death in the world. We aimed to characterize the long-term trends in mortality and disease burden of selected neurological disorders and quantitatively analyze the contributions of demographic and non-demographic factors on the mortality of selected neurological disorders in Shanghai, China, 1995–2018. Methods: Mortality data were derived from the Vital Statistics System of Pudong New Area, Shanghai, China, during 1995–2018. Temporal trends for the mortality rates and burden of selected neurological disorders were analyzed by Joinpoint Regression Program. Years of life lost (YLL) was used to analyze the burden of disease. The increasing mortality rates related to demographic and non-demographic factors were estimated by the decomposition method. Results: A total of 4432 deaths from selected neurological disorders occurred during 1995–2018, accounting for 0.98% of total deaths. The crude mortality rates (CMR) and age-standardized mortality rates (ASMRW) of neurological disorders were 7.14/105 person–years and 4.08/105 person–years, respectively. Extrapyramidal and movement disorders, other degenerative diseases of the nervous system, and episodic and paroxysmal disorders were the three leading causes of mortality and YLL of selected neurological disorders. The CMR, ASMRW, and rate of YLL for deaths from selected neurological disorders showed significantly increasing trends in males, females, and the total population during 1995–2018 (all P < 0.001). The contribution rates of increased values of CMR related to demographic factors were more evident than non-demographic factors. Conclusion: The mortality rate and rate of YLL for death from selected neurological disorders increased significantly during 1995–2018 in Pudong New Area, Shanghai. The demographic factors, particularly aging, might be related to an increase in the mortality of neurological disorders. More effective prevention strategies are needed to prevent the aging-related death and burden from neurological disorders in the future.